Risk factors of oesophageal cancer at health facilities in Addis Ababa, Ethiopia: Unmatched case control study - Dessalegn, Berhe; Enqueselassie, Fikre; Kaba, Mirgissa; Assefa, Mathewos; Addissie, Adamu (Frontiers in Oncology, 2022)
Background: Oesophageal carcinoma is one of the most common cancers in Ethiopia. Its occurrences vary among regional states of the country. The identification of local risk factors of oesophageal cancer will make it simple to design a focused intervention. On local risk factors, there is, however, a shortage of empirical evidence. Therefore, the aim of study was to identify local risk factors. Methods: An unmatched case control study design was employed. From February 2019 to August 2020, 338 histologically confirmed cases and 338 controls were recruited consecutively from six health facilities in Addis Ababa, Ethiopia’s capital city. To collect data from the cases and the controls, face to face interviews were conducted. Epi-info version 7 was used to enter and cleaned data, and SPSS version 23 was used to analyze it. The odds ratio was calculated based on hierarchal model multivariable logistic regression, and statistically significance was declared at p-value of <0.05. Results: The mean (SD) age of the cases and the controls was 54.3 ± 12.5 years old and 40.2 ± 13.7 years old, respectively. The odds of oesophageal cancer was significantly higher among older ages (OR =11.0, 95% CI [6.60, 20.91]), rural residents (OR = 4.2, 95% CI [1.04, 16.80]), and those who had history of smoking (OR =1.3, 95% CI [1.12, 1.60]), khat chewing (OR = 4.0, 95% CI [2.50, 6.60]), raw meat consumers (OR = 2.6, 95% CI [1.75, 3.90]). Increasing monthly income (OR = 0.2, CI 95% [0.09, 0.49]) and a habit of eating fruits or vegetables (OR = 0.49, 95% CI [0.32, 0.76]) were associated with lower risks. Conclusions: Tobacco smoking, khat chewing, age, residency, and red raw meat consumption were discovered to be positive predictors of oesophageal cancer, whereas fruit or vegetable consumption and higher monthly income were discovered to be inversely associated. It is advised to avoid the use of khat and tobacco, as well as to avail fruits and vegetables in dish